Archaeological Site Impacts in the Hambantota District, Sri Lanka: Markov Chain/GIS/RS-based Analysis of Land Use and Change Detection, 1972-2014 - Stimers, M.J.; W.P., Fernando,; Lenagala, S.K. (IJRDO-Journal of Applied Science, 2019)
The Greater Hambantota area features a variety of archaeological sites and monuments carrying considerable importance in Sri Lankan history.  Recent expansion of land-use patterns in the Hambantota District shows a rapid encroachment on ancient cultural landscapes in the area, and has obliterated almost all tangible evidence of important sites that remain above ground. Cultural inheritance is an essential component of sustainable development in all societies, and gaining insights from this point view, the present study justifies the suitability of the Hambantota district as a unit of analysis. Real knowledge of the cultural landscape and understanding landscape changes could facilitate and improve prediction concerning the current and future condition of landscapes, and this is especially important for urban planners developing urban plans. The present research attempts to evaluate and present the spatial determinants and other related factors exerting influence on the changing land use patterns in the Greater Hambantota area. Here we evaluate land use changes during the period 1972 – 2014, and also offer insight into possible future land uses by way of a Markov Chain analysis.